STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMP NEGERI 2 SIGLI KABUPATEN PIDIE - Marjuani .; Yusrizal .; Khairuddin . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2015)
Abstract: The strategic role of the school principal can be done by improving the quality of Human Resources (SDM) in accordance with the needs of schools and education specifically, by making adjustments to education and schools are able to thrive and maju. The purpose of this study was to determine the principal strategy in improving teacher performance, with include: (1) Discipline;     (2) Competence; and (3) Responsibility of teachers. Through a qualitative approach with descriptive methods, techniques of data collection is done through interviews, observation, and documentation. Subjects were principals, teachers and supervisors at SMP Negeri 2 Sigli Kabupatem Pidie. Research results found: (1) The principal strategy in addressing the problem of teachers who lack the discipline that is by calling the teacher personally to take advice, so it does not negatively impact other teachers, and invited together to improve the discipline that can be exemplified by the students ; (2) The principal strategy in addressing the problem of teachers who lack competence is by calling the teachers concerned to be fostered, guidance and training to use innovative media so that learners have a high motivation in participating in the classroom; and (3) The principal strategy in addressing the teacher's responsibility is by way of training for teachers who have not been regular in menjabar lesson plans and syllabi, even principals have recourse to the supervisor or the relevant office to socialize teachers in improving the administration of the teacher. It is expected that supervisors in order to direct and supervise principals in improving teacher performance on discipline, competence, and responsibility of teachers to effectively and efficiency so that performance can be improved.Keywords: Strategy Principal and Teacher Performance.Abstrak: Peran strategis kepala sekolah dapat dilakukan melalui peningkatan kualitas Sumber Daya Manusia (SDM) sesuai dengan kebutuhan sekolah dan dunia pendidikan secara spesifik, dengan melakukan penyesuaian agar pendidikan dan sekolah mampu untuk berkembang dan maju.Tujuan penelitian ini adalah untuk mengetahui strategi kepala sekolah dalam meningkatkan kinerja guru, dengan meliputi: disiplin; kompetensi; dan tanggung jawab guru. Melalui pendekatan kualitatif dengan metode deskriptif, teknik pengumpulan data dilakukan melalui wawancara, observasi, dan studi dokumentasi. Subjek penelitian adalah kepala sekolah, guru dan pengawas pada SMP Negeri 2 Sigli Kabupaten Pidie. Hasil penelitiannya ditemukan: (1) Strategi kepala sekolah dalam mengatasi masalah guru yang kurang disiplin yaitu dengan cara memanggil guru yang bersangkutan secara personal untuk dinasehati, sehingga tidak berdampak negatif terhadap guru lain, dan diajak bersama-sama untuk meningkatkan disiplin supaya dapat dicontohi oleh siswa; (2) Strategi kepala sekolah dalam mengatasi masalah guru yang kurang kompetensi yaitu dengan memanggil guru yang bersangkutan untuk dibina, pengarahan dan pelatihan agar mempergunakan media yang inovatif sehingga peserta didik memiliki motivasi tinggi dalam mengikuti pembelajaran di kelas; dan (3) Strategi kepala sekolah dalam mengatasi masalah tanggung jawab guru yaitu dengan cara mengadakan pelatihan bagi guru yang belum teratur dalam menjabar RPP dan silabus, bahkan kepala sekolah meminta bantuan kepada pengawas atau dinas terkait untuk mensosialisasikan guru dalam peningkatan administrasi guru. Diharapkan kepada pengawas agar dapat mengarahkan dan mengawasi kepala sekolah dalam meningkatkan kinerja guru tentang disiplin, kompetensi, dan tanggung jawab guru secara efektif dan efesiensi sehingga kinerjanya dapat ditingkatkan.Kata kunci: Strategi Kepala Sekolah dan Kinerja Guru.